2021
DOI: 10.3390/plants10010165
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Molecular Traits Associated with Nitrogen Uptake under Limited Nitrogen in Soft Red Winter Wheat

Abstract: A sufficient nitrogen (N) supply is pivotal for high grain yield and desired grain protein content in wheat (Triticum aestivum L.). Elucidation of physiological and molecular mechanisms underlying nitrogen use efficiency (NUE) will enhance our ability to develop new N-saving varieties in wheat. In this study, we analyzed two soft red winter wheat genotypes, VA08MAS-369 and VA07W-415, with contrasting NUE under limited N. Our previous study demonstrated that higher NUE in VA08MAS-369 resulted from accelerated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…This last result would seem to confirm the findings of other experiments on wheat and other species that have shown close relationships between the overall N accumulated in the canopy and the leaf area [44,45]. Furthermore, other studies have highlighted significant relationships between root traits (length, distribution, and density in the different soil layers), grain yield, nutrient uptake capacity, and water use efficiency [23,[46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 88%
“…This last result would seem to confirm the findings of other experiments on wheat and other species that have shown close relationships between the overall N accumulated in the canopy and the leaf area [44,45]. Furthermore, other studies have highlighted significant relationships between root traits (length, distribution, and density in the different soil layers), grain yield, nutrient uptake capacity, and water use efficiency [23,[46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 88%
“…Our results also confirmed these findings that the increased kernel weight could balance the decrease in grain number per unit area (Giunta et al, 2019), and the genetic variation in grain protein deviation was mainly determined by post-anthesis N uptake, rather than N remobilization efficiency (Mosleth et al, 2015). Furthermore, previous results have shown that post-anthesis N uptake was determined by genotype, and correlated positively with the root nitrate reductase gene (Zhao et al, 2013) and root system vigor (Nigro et al, 2019;Lamichhane et al, 2021). Further analysis is required to analyze the contribution of N capture genes to grain protein deviation.…”
Section: Post-anthesis N Uptake Contributed To Simultaneous Improveme...mentioning
confidence: 99%
“…According to Bonnave and Bertin (2018), higher NUE is also responsible for conferring salt resilience in rice. It has been revealed that salt-tolerant wheat lines retained higher yield and yield-related attributes, as well as the maximum NUE indexes, compared to salt-sensitive wheat lines, which could be accountable to the greater N uptake proficiency in the tolerant genotype (Lamichhane et al, 2021). Nitrogen application at the proper dose and timings may also minimize N losses and increase efficiency.…”
Section: Regulation Of Nitrogen Metabolism and Nitrogen Use Efficienc...mentioning
confidence: 99%